WAQF FUND IN MALAYSIA: A BIBLIOMETRIC ANALYSIS - Ramlan Mustapha; Mohd Nasir Ayub; Surita Hartini Hassan; Norma Aisyah Malkan; Maziah Mahmud; Asjad Mohamed (Journal of Islamic, Social, Economics and Development, 2023)
The Waqf Fund has been the subject of research because of its potential to contribute to the growth of socioeconomic development. Though there is a great deal of written information concerning this waqf fund, researchers' aims and findings are all over the map. Therefore, we conduct a bibliometric analysis of waqf literature to understand the pattern and direction of research on Waqf broadly. We collect 944 articles, and reviews on Waqf extracted from the Google Scholar database, covering a period exceeding 5 years from 2015 until 2020. Microsoft Excel, VOS viewer, and Harzing tools are used for citation, content, and network studies. The bibliometric evaluation was supplemented by a comprehensive literature search of recent papers. In addition to uncovering the leading scientific figures in waqf literature, this review finds that the majority of scholars focusing on waqf hail from Malaysia and have published extensively on the topic. As a result, we identify 10 research themes (clusters) for waqf find studies. This is the first study to give a bibliometric assessment of the literature regarding waqf funds in Malaysia. The purpose of this review is to address gaps in the existing research and propose directions for future research. Early-career Islamic finance academics may benefit from these directions.